Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/21691401.2018.1493489
|View full text |Cite
|
Sign up to set email alerts
|

Xenogeneic bone matrix immune risk assessment using GGTA1 knockout mice

Abstract: Homeotransplantation of bones for replacement therapy have been demonstrated reliably in clinical data. However, human donor bones applicable for homeotransplantation are in short supply, which facilitates the search for suitable alternatives, such as xenografts grafts. The α-Gal antigen-related immune risk of xenografts directly affects the safety and effectiveness of the biomaterials and limits their applications in the clinic. The immune risk can be prevented by depletion or breaking anti-Gal antibody prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Our results demonstrated that T1 stimulate a higher antiα-Gal antibody expression level in G/i DKO mice compared with the T2 group, which was similar to our previous findings using GGTA1 KO mice [17]. However, T1 implantation did not cause a significant increase in anti-Gal IgM and IgA levels in GGTA1 KO mice [17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results demonstrated that T1 stimulate a higher antiα-Gal antibody expression level in G/i DKO mice compared with the T2 group, which was similar to our previous findings using GGTA1 KO mice [17]. However, T1 implantation did not cause a significant increase in anti-Gal IgM and IgA levels in GGTA1 KO mice [17].…”
Section: Discussionsupporting
confidence: 91%
“…Sun et al assessed the immunotoxicity of xenogeneic bone by embedded materials into the intermuscular space of Balb/c mice was insufficiently scientific [29]. Third, to further verify the applicability of G/i DKO mice as a model for the assessment of immune responses of xenoimplants, G/i DKO mice were implanted with raw lyophilized bone substitutes (T1, containing high Gal antigens, ð8:14 ± 3:17Þ × 10 12 /mg) and Guanhao Biotech bone substitutes (T2,~50% decreased α-Gal antigen relative to T1 [17]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported immune effects induced by xenogeneic material implantation in GTKO mice also included the elevation of cytokine levels. Xenogeneic bone tissue had induced more than 10 times increase in anti-Gal IgG level of GTKO mice compared with the blank control, accompanied by a significant increase in serum IL-12p70 and IL-4 content [ 20 ]. However, at 4 weeks after implantation of the DCM, there were no significant differences in serum IFN-γ, IL-4 and IL-12p70 levels between the GTKO mice and the blank control group, although the elevation of the anti-Gal IgG antibody stimulated by residual αGal antigen contained in the DCM occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The αGal contents of fresh corneal matrix and DCM were quantitatively detected by an inhibitory enzyme-linked immunosorbent assay (ELISA) [ 20 ]. Firstly, the lysates of corneal matrix were prepared by homogenized in lysis buffer containing 1% protease inhibitor PMSF using a homogenizer (Benchmark D1000-E, USA), incubating at room temperature for 1–3 h, and making sure that there were no obvious solid matters and the α-Gal antigen was completely exposed.…”
Section: Methodsmentioning
confidence: 99%